2020
DOI: 10.3390/agronomy10030334
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Catch Crops and Tillage Systems on Selected Physical Properties and Enzymatic Activity of Loess Soil in a Spring Wheat Monoculture

Abstract: This study was aimed at comparing physical soil quality parameters and soil enzymatic activity in a three-year spring wheat monoculture affected by the incorporation of biomass of selected catch crops into the soil using two systems of tillage (conventional plough tillage and conservation tillage). We tested the suitability of the following catch crop plants: white mustard, lacy phacelia, and mixed legumes (faba bean + spring vetch) and compared these to the control treatment. This research was carried out in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 44 publications
(58 reference statements)
2
24
0
Order By: Relevance
“…Some authors found that a CC intercrop stimulated higher soil moisture only in the top layer (0-10 cm), while their effect on moisture in deeper layers turned out to be insignificant [249,250]. On the other hand, Harasim et al [218] proved an increase in soil moisture at a depth of 15 to 20 cm with legume CCs cultivated as intercrops. RIL directly affects the availability of water for cultivated plants during the growing season, especially at a depth of 90 cm [251].…”
Section: Effect Of Legume Ccs On Soil Water Managementmentioning
confidence: 99%
See 3 more Smart Citations
“…Some authors found that a CC intercrop stimulated higher soil moisture only in the top layer (0-10 cm), while their effect on moisture in deeper layers turned out to be insignificant [249,250]. On the other hand, Harasim et al [218] proved an increase in soil moisture at a depth of 15 to 20 cm with legume CCs cultivated as intercrops. RIL directly affects the availability of water for cultivated plants during the growing season, especially at a depth of 90 cm [251].…”
Section: Effect Of Legume Ccs On Soil Water Managementmentioning
confidence: 99%
“…Residues of CC plants, including legume CCs, improve soil structure by influencing soil strength, porosity and hydraulic properties. They also increase the diffusion capacity of soil air, as well as the formation of soil aggregates (basic units of soil structure) [217][218][219] (Table 3). [222] no legume CCs mixture of S. cereale L., P.…”
Section: Effect Of Legume Ccs On Soil Structure and Aggregationmentioning
confidence: 99%
See 2 more Smart Citations
“…Agronomic measures include, for example, the cultivation of cover crops, direct seeding, or no or no-turn tillage without ploughing. These measures have a rather indirect effect on the prevention of soil compaction by stimulating soil biota, thereby improving aggregate stability and thus the resilience of soils [2,[23][24][25]. As a further side effect, the number of machine passes is reduced and the generation of a so-called "plough sole" is avoided.…”
Section: Measures To Prevent or Mitigate Soil Compactionmentioning
confidence: 99%